Radiological follow-up of osteonecrosis lesions in children and adolescents with Hodgkin lymphoma - Aarnivala, Henri; Giertz, Mia; Michelsen, Sascha Wilk; Björklund, Caroline; Englund, Annika; Grönroos, Marika; Hjalgrim, Lisa Lyngsie; Huttunen, Pasi; Niinimäki, Tuukka; Penno, Eva; Pokka, Tytti; Pöyhönen, Tuuli; et al. (Wiley-Blackwell, 2025)
Osteonecrosis (ON) is a common complication of glucocorticoid-based Hodgkin lymphoma (HL) treatment, but the natural evolution and prognosis of ON lesions remain poorly understood. We describe the radiological evolution of ON lesions identified in a Nordic population-based cohort of paediatric HL patients. Magnetic resonance images of suspected ON lesions were centrally reviewed to confirm ON diagnosis and grade the ON lesions according to the Niinimäki classification. The study included 202 ON lesions in 46 patients, of which 77 were joint lesions. Follow-up images were available for 146/202 lesions, with a mean follow-up time of 28 months. During follow-up, 71% of the lesions remained stable, 26% improved or resolved, and 3% progressed. A higher ON grade at diagnosis was associated with a lower likelihood of spontaneous resolution. The likelihood for resolution of ON decreased by 50% for each year of added patient age, when adjusted for sex, ON location, and symptoms. Hip ON showed less spontaneous improvement compared with other joints, and the risk for surgery was 13-fold in hip ON. Grades 3-4 joint ON has the potential to either progress or resolve, warranting follow-up in patients with severe symptoms. Research on secondary prevention should be directed at grade 3-4 joint ON.